Foster - Keegan, Claire (New York, NY Grove Press, an imprint of Grove Atlantic, 2022)
"An international bestseller and one of The Times's "Top 50 Novels Published in the 21st Century," Claire Keegan's piercing contemporary classic Foster is a heartbreaking story of childhood, loss, and love, now released as a standalone book for the first time ever in the US. It is a hot summer in rural Ireland. A child is taken by her father to live with relatives on a farm, not knowing when or if she will be brought home again. In the Kinsellas' house, she finds an affection and warmth she has not known and slowly, in their care, begins to blossom. But there is something unspoken in this new household-where everything is so well tended to-and this summer must soon come to an end. Winner of the prestigious Davy Byrnes Award and published in an abridged version in the New Yorker, this internationally bestselling contemporary classic is now available for the first time in the US in a full, standalone edition. A story of astonishing emotional depth, Foster showcases Claire Keegan's great talent and secures her reputation as one of our most important storytellers"--
"First published in the United Kingdom in 2010"--Title page verso.
111058
Keywords: Foster home care -- Ireland -- Fiction; Novels